Project Cost Estimation Using a Stepwise Approach: a Case Study of an Infrastructure Project in Gresik Regency, East Java - Siswoyo, Siswoyo; Soepriyono, Soepriyono; Suharso, Akbar Bayu Kresno; Saurina, Nia; Retnawati, Lestari (Universitas Negeri Semarang, 2023)
There are many studies related to cost estimation applied in a project, but only a few employ using “stepwise” method. This approach is expected to assist in solving complex problems by establishing a criteria hierarchy, subjectively assessed by interested parties, and incorporating various considerations to develop weights or priorities. The foundation of the stepwise approach relies on well-documented findings, which assert that 80% of the total project cost corresponds to the 20% most expensive components of the work. The research systematically collected data for project development estimates based on the bill of quantities from each year, as well as the HSPK (activity main unit price) in Gresik Regency from 2016 to 2018. This research aims to develop a conceptualized estimation model that provides clear, rapid, and relatively accurate initial project cost information. The results of this research include analysis of stepwise approach on cost realization, analysis of accuracy of the cost estimation model for buildings using the stepwise method, and an analysis of the cost of road and bridge infrastructure projects to facilitate completion in Gresik Regency. The research concludes that the analysis of the Cost Significant Model's impact on cost realization in the Public Works and Spatial Office's Highways Division in Gresik Regency has resulted in a cost estimation model for road development with an accuracy range from -12.7% to 16.0%, with an average accuracy rate of 0.59%. Additionally, there is a very strong correlation (R) of the independent variable (work in Division 2) and the total development cost, indicating that fluctuations in the cost of significant components are closely linked to changes in the overall development cost. The analysis of infrastructure project costs related to roads and bridges for project completion revealed that the highest value among independent variables is associated with Division 7, at Rp. 4,403,054 per m2. This suggests that the cost of Division 7 work is the most influential, while Division 1 (X1) has the lowest cost, at Rp. 35,589 per m2. Furthermore, there is a work component with zero cost, namely, Division 4 works.